Introducing learner infrastructural capabilities into information systems success model using e-learning - Atanda, Balogun Naeem; Ahlan, Abdul Rahman; Veronica, Omenogo Mejabi; Wasiu, Olayiwola Bello (University of Sindh, Jamshoro, 2017)
The study introduces learner infrastructural capabilities into the field of information systems success. The introduction of this construct in information systems success is important due to lack of consideration for the individual infrastructural ability that has not been addressed by the success factors with respect to individual, environment, developing countries and digital divide. An explanatory mixed method research design is considered using questionnaire for the survey and an open-ended interview for data collection. Four hundred and twelve responses were used from survey and ten people for interview. The Information Systems success dimensions include system use, system quality, service quality, content quality, user satisfaction and net benefit and the learner infrastructural capabilities which include the computer ownership, internet access and energy generation. The study found a good model fit for learner infrastructural capabilities when dimensions of information systems success model of DeLone and McLean are used, forming a success model that inculcate the individual Information Systems infrastructure.